Additionalto Synthetic Fiber On Materials Plastic Injection To Minimize Product Defects. Issue 1 (February 2021) - Azharul, Firmansyah; Rahmawati,; Harno,; Wilarso,; Mujiarto,
Abstract: Plastic injection molding process in the manufacture of air gun components, namely butt stock gun, and pump handles, product defects are still often found, some of the causes include: burning (burning), lack of material (short shots), and cracking products (cracking), this resulting in not achieving production targets and sales targets. The purpose of this research is to find out the root cause of failure of air gun component products. The method in this problem, plastic injection materials need to be added synthetic fibers to get the visual appearance, tensile strength, modulus of elasticity, and the desired hardness, by utilizing recycled material products. The results showed visually the addition of recycled materials and synthetic fibers did not affect appearance, in economic terms the more recycled materials added the cheaper the cost of material procurement. The addition of recycled material weighing 50% of the original material and 2.5% synthetic fiber from the total amount of material to be processed, is expected to increase the tensile strength, modulus of elasticity and desired hardness. Therefore, this addition of fiber obtains a more accurate comparison of product quality and quantity with a lower product defect rate, and is able to reduce production costs.